Development and Quasi-Experimental Evaluation of a Visual Textbook for Learning Theories in Teacher Education - Safitri, Baiq Rina Amalia; Verawati, Ni Nyoman Sri Putu; Azmi, Irham (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study developed and evaluated a visually structured textbook for the Learning Theories course in teacher education, addressing the limited empirical evidence on visually oriented core textbooks for concept-heavy theory courses. A Research and Development approach using the ADDIE framework guided the analysis, design, development, expert validation, implementation, and evaluation stages. Participants were 56 first-semester Information Technology Education students at Universitas Pendidikan Mandalika, assigned by intact class to an experimental group using the visual textbook (n = 28) and a control group using a conventional printed textbook (n = 28). Data were collected through expert-validation questionnaires, a student-response questionnaire, and a pretest–posttest Course Achievement Test. Content, media, and practitioner evaluations ranged from 85% to 90%, placing the textbook in the highly valid category. Students also reported favorable perceptions of readability, visual presentation, relevance, and support for independent study. After controlling for pretest achievement, ANCOVA showed a significant group effect on posttest scores, F(1,53) = 1380.908, p < .001, partial η² = .963. The experimental group also achieved a higher normalized gain (M = 0.640, SD = 0.031) than the control group (M = 0.303, SD = 0.050), with Welch’s t(45.077) = 30.283, p < .001. These findings indicate that, within the present quasi-experimental context, use of the visually structured textbook was associated with substantially greater learning achievement and positive perceived instructional support. Further multi-institutional and longitudinal studies are needed to assess generalizability, retention, and underlying learning mechanisms.